Pediatric endonasal dacryocystorhinostomy: A multicenter series of 116 cases. (3rd September 2017) - Chan, WengOnn; Wilcsek, Geoff; Ghabrial, Raf; Goldberg, Robert Alan; Dolman, Peter; Selva, Dinesh; Malhotra, Raman
ABSTRACT: We report our experience with pediatric endonasal dacryocystorhinostomy (DCR). Multicenter, retrospective, noncomparative study. Cases of pediatric endonasal DCR during 2006–2011 were included from six oculoplastic units. Patients over the age of 16 years were excluded. The outcomes of pediatric endonasal DCR are presented. Indication for surgery, demographics, previous interventions, intraoperative or postoperative complications, follow-up duration, and success rate (defined as significant improvement of epiphora) were evaluated. In total, 116 endonasal DCRs were performed for 103 patients. The mean follow-up period was 8 months (range 3 months to 4 years), with 1 patient lost to follow-up. There were 48 males (mean age 5 years and 9 months) and 50 females (range of 4 months to 16 years), with a total of 98 cases of congenital nasolacrimal duct obstruction (CNLDO) (84.5%) and 18 cases of acquired nasolacrimal duct obstruction (ANLDO) (15.5%). Previous interventions included probing 75.9% (88/116), massaging 43.1% (50/116), and intubation 39.7% (46/116). There were no intraoperative complications. There was one case of postoperative pyogenic granuloma. There were no cases of postoperative infection and postoperative hemorrhage. Ninety percent of procedures were considered successful. Complete symptom resolution was observed in 78% (90/116), significant improvement in 12% (14/116), partial improvement in 2% (2/116), and no improvement in 8% (9/116). In our series, we demonstrated that endonasal DCR is a safe operation and has an overall success rate of 90% for pediatric NLDO.